PENDAMPINGAN DIGITALISASI SISTEM ADMINISTRASI DESA BERBASIS APLIKASI DI DESA SUKACAI KECAMATAN JIPUT KABUPATEN PANDEGLANG - Gagah Dwiki Putra Aryono; Sigit Auliana; Asep Sapaatullah; Maman Masyhuri; Achmad Dwi Saputro (Merwinspy Publisher, 2025)
This community service initiative seeks to support the implementation of a village service application system based on the Laravel framework in Sukacai Village, Jiput District, Pandeglang Regency. The system is intended to improve the efficiency and transparency of village administrative processes by digitizing them. The methods involve training local staff, installing the application, and providing ongoing monitoring during the implementation phase. The desired outcomes include a system that enables village officials to manage public services more effectively, leading to faster, more reliable services for the community. In addition, this project emphasizes capacity building to ensure that village officials not only use the system but can maintain it independently in the long term. By improving digital literacy among village staff and fostering a more tech-savvy environment, the system's sustainability and adaptability are expected to benefit the community at large. Through these efforts, the overall goal is to create a model for other rural areas to follow in improving public services with technology.